2013
DOI: 10.3389/fchem.2013.00040
|View full text |Cite
|
Sign up to set email alerts
|

Chicoric acid: chemistry, distribution, and production

Abstract: Though chicoric acid was first identified in 1958, it was largely ignored until recent popular media coverage cited potential health beneficial properties from consuming food and dietary supplements containing this compound. To date, plants from at least 63 genera and species have been found to contain chicoric acid, and while the compound is used as a processing quality indicator, it may also have useful health benefits. This review of chicoric acid summarizes research findings and highlights gaps in research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 154 publications
(249 reference statements)
3
81
0
1
Order By: Relevance
“…Kour and Bani demonstrated that ChA has a protective effect on chronic restraint stress . Recently, ChA has been shown to have anti‐cancer, anti‐obesity, and anti‐diabetic properties . A significant reduction in acute alcohol‐induced steatosis was observed on oral intake of chicoric acid in mice through interfering with inducible nitric oxide synthase (iNOS) in the liver .…”
Section: Introductionsupporting
confidence: 86%
“…Kour and Bani demonstrated that ChA has a protective effect on chronic restraint stress . Recently, ChA has been shown to have anti‐cancer, anti‐obesity, and anti‐diabetic properties . A significant reduction in acute alcohol‐induced steatosis was observed on oral intake of chicoric acid in mice through interfering with inducible nitric oxide synthase (iNOS) in the liver .…”
Section: Introductionsupporting
confidence: 86%
“…This metabolite has been proposed as an indicator compound for quality control due to its instability and rapid degradation when compared to other secondary metabolites within plant materials [9, 18]. Enhancement due to the incorporation of methanol as a cosolvent during PHWE can be associated with interactions based on polarity.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that chicoric acid possesses various functional properties including antioxidant, antivirus and immunoregulation. [28,29] Particularly, chicoric acid is a potent inhibitor of the integrase of the Type 1 human immunodeficiency virus (HIV-1). [30] Additionally, Lee and Scagel [28] indicated that chicoric acid helps a plant protect itself from insects and infection from viruses, bacteria, fungi, and nematodes and that it aids in wound healing in plants after mechanical damage.…”
Section: Rp-hplc Analysis Of Phenolic Compoundsmentioning
confidence: 99%